Local and remote drivers of increased variability in extreme wildfire conditions in Southeastern Australia - Kiwook Kim; Myong-In Lee; Seungseok Lee; Nakbin Choi; Fei-Fei Jin; Seung-Ki Min; Jonghun Kam (Agricultural and Forest Meteorology, 2026)

Busan Atmosphere Cryosphere Ocean Conference BACO-25: Our Interconnected Earth - Keith Alverson; Silvia Blanc; Richard Essery; Myong-In Lee (Advances in Atmospheric Sciences, 2026)

Corrigendum to ‘Comparative evaluation of surface-level PM2.5 modeling across Northeast Asia: relevance for regulatory and scientific applications’ [Environ. Pollut. 377 (2025) 126428] - Hyeon-Kook Kim; EunRyoung Kim; Chang-Keun Song; Jae-Ho Choi; Ganghan Kim; Myong-In Lee; Yujin J. Oak; Rokjin J. Park; Ilhan Ryoo; Seung-Muk Yi; Kyung-Mi Lee; Hyeok-Gi Cheo; et al. (Environmental Pollution, 2026)

A Multiphysics Method for Increasing Model Background Error in the Aerosol Data Assimilation with an Ensemble Kalman Filter - Seunghee Lee; Myong-In Lee; Wooseok Kang (Atmospheric Pollution Research, 2026)

Comparative evaluation of surface-level PM2.5 modeling across Northeast Asia: relevance for regulatory and scientific applications - Hyeon-Kook Kim; EunRyoung Kim; Chang-Keun Song; Jae-Ho Choi; Ganghan Kim; Myong-In Lee; Yujin J. Oak; Rokjin J. Park; Ilhan Ryoo; Seung-Muk Yi; Kyung-Mi Lee; Hyeok-Gi Cheo; et al. (Environmental Pollution, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Insights and machine learning predictions of harmful algal bloom in the East China Sea and Yellow Sea - Jiyi Jang; Sang-Soo Baek; Daehyun Kang; Yongeun Park; Mayzonee Ligaray; Seung Ho Baek; Jin Yong Choi; Bum Soo Park; Myong-In Lee; Kyung Hwa Cho (Journal of Cleaner Production, 2024)

Significant relationship between Arctic warming and East Asia hot summers - Da‐Seul Kim; Sang‐Yoon Jun; Myong‐In Lee; Jong‐Seong Kug (International Journal of Climatology, 2022)
Arctic warming is of growing interest because it could affect midlatitude climates. Even though numerous studies have paid attention to the relationship between Arctic warming and the midlatitude climate in winter, the influence of Arctic warming on the summer conditions has not been examined in depth. Here we identify a significant relationship between East Asia hot summers and Arctic warming over the Barents and Kara seas. To represent Arctic warming, we define a combined index by simply differencing the normalized surface air temperature and sea‐ice indices. We found that the combined index in July has significantly high correlations with the temperatures in China, Korea, and Japan. While the teleconnection mechanism is not completely revealed, it is evident that warming over the Barents and Kara seas is accompanied by the local development of an anomalous anticyclone and downstream wave trains, which yield a strong anticyclonic circulation over East Asia and the North Pacific. The anticyclonic circulation persists and intensifies until August, which leads to hot summer conditions in East Asia with warm advection and enhanced shortwave radiation. Our results suggest that Arctic climate conditions can be used as a useful precursor of East Asia temperature variations even in summer.

Population genomics study for the conservation management of the endangered shrub Abeliophyllum distichum - Jung-Hoon Lee; Homervergel G. Ong; Bo-Yun Kim; Yong-In Kim; Eui-Kwon Jung; Myong Gi Chung; Young-Dong Kim (Conservation Genetics, 2022)
Natural monuments are IUCN Category III protected areas that play an important role in biodiversity conservation as they provide species refuge and allow species migration. Despite their status, natural monuments are often confined to cultural and fragmented landscapes due to anthropogenic land-use demands. In this population genomic study, we surveyed 11 populations of the endemic shrub Abeliophyllum distichum Nakai (Oleaceae), including five natural monument habitats, covering its range-wide distribution in South Korea. Using 2,254 SNPs as markers, our results showed a mean expected heterozygosity ( He ) of 0.319, with populations in the central distribution showing significantly higher He than those at the periphery. There was no significant heterozygote deficiency and inbreeding among studied populations overall ( F IS = −0.098), except for a single natural monument population (GS-NM147). Population structure and differentiation was moderate to high ( F ST = 0.196), while recent gene flow between populations appeared weak, which can be attributed to the fragmented distribution and the outcrossing mating system of the heterostylous plant. Based on these findings, we provide suggestions for the population conservation and management of this endangered species.

Importance of ocean initial conditions of late autumn on winter seasonal prediction skill in atmosphere–land–ocean–sea ice coupled forecast system - Joonlee Lee; Myong-In Lee; Joong-Bae Ahn (Climate Dynamics, 2022)

Korea Institute of Ocean Science and Technology Earth System Model and Its Simulation Characteristics - Gyundo Pak; Yign Noh; Myong-In Lee; Sang-Wook Yeh; Daehyun Kim; Sang-Yeob Kim; Joon-Lee Lee; Ho Jin Lee; Seung-Hwon Hyun; Kwang-Yeon Lee; Jae-Hak Lee; Young-Gyu Park; et al. (Ocean Science Journal, 2021)

Representation of Tropical Cyclones by the Modern-Era Retrospective Analysis for Research and Applications Version 2 - Hyerim Kim; Myong-In Lee; Sungyoon Kim; Young-Kwon Lim; Siegfried D. Schubert; Andrea M. Molod (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Recent changes in heatwave characteristics over Korea - Donghyuck Yoon; Dong-Hyun Cha; Myong-In Lee; Ki-Hong Min; Joowan Kim; Sang-Yoon Jun; Yonghan Choi (Climate Dynamics, 2020)

Effects of surface vegetation on the intensity of East Asian summer monsoon as revealed by observation and model experiments - Seonju Lee; Myong‐In Lee (International Journal of Climatology, 2020)
This study investigates the effects of surface vegetation density on the East Asian summer monsoon (EASM). The analysis using observation and reanalysis data reveals that the increase of vegetation drives a dipole pattern in the precipitation anomalies where the precipitation in Northeast Asia tends to increase, whereas the precipitation in southern China and East China Sea tends to decrease. The model sensitivity experiments confirm the mechanism of regional monsoon circulation changed by changes in surface vegetation density, in which enhanced vegetation leads to an increase of surface evapotranspiration and a decrease of surface temperature over land. The decrease in precipitation over southern China and East China Sea is attributed to the slow‐down of EASM circulation due to the reduction in thermal contrast between the continent and the ocean. The results suggest that the surface vegetation can change the local thermal conditions and induce the dynamical process in broader scale to change the precipitation response.

Improved representation of the diurnal variation of warm season precipitation by an atmospheric general circulation model at a 10 km horizontal resolution - Hyerim Kim; Myong-In Lee; Dong-Hyun Cha; Young-Kwon Lim; William M. Putman (Climate Dynamics, 2019)

ENSO influence on the dynamical seasonal prediction of the East Asian Winter Monsoon - Daehyun Kang; Myong-In Lee (Climate Dynamics, 2019)

Inter‐annual variation of tropical cyclones simulated by GEOS‐5 AGCM with modified convection scheme - Eunkyo Seo; Myong‐In Lee; Dongmin Kim; Young‐Kwon Lim; Siegfried D. Schubert; Kyu‐Myong Kim (International Journal of Climatology, 2019)
The Goddard Earth Observing System version 5 (GEOS‐5) global climate model with a 50‐km horizontal resolution is forced by observed sea surface temperature (SST) to examine the fidelity of the seasonal‐mean and inter‐annual variation of tropical cyclones (TCs) in the western North Pacific (WNP) and the North Atlantic (NATL). The standard Relaxed Arakawa Schubert (RAS) deep convection scheme is modified to improve the representation of TCs, where the scheme implements a stochastic limit of the cumulus entrainment rate. The modification drives mid‐ and upper‐tropospheric cooling and low‐ to mid‐tropospheric drying in the background state, which tends to increase atmospheric instability. This enables the model to increase convective variability on an intra‐seasonal timescale and improve the simulation of intense storms. Five‐member ensemble runs with the modified RAS scheme for 12 years (1998–2009) exhibit realistic spatial distributions in the climatological‐mean TC development area and their pathways over WNP and NATL. The GCM is able to reproduce the inter‐annual variation of accumulated cyclone energy (ACE) by prescribing yearly varying observed SST even though the individual TC intensity is still underpredicted. A sensitivity of TC activity to El Niño–Southern Oscillation (ENSO) phase is also reproduced realistically over WNP in terms of the spatial pattern changes in the main development region and TC pathways. However, the model exhibits a notable deficiency in NATL in reproducing the observed inter‐annual variation of TC activity and the sensitivity to the ENSO.

Impact of soil moisture initialization on boreal summer subseasonal forecasts: mid-latitude surface air temperature and heat wave events - Eunkyo Seo; Myong-In Lee; Jee-Hoon Jeong; Randal D. Koster; Siegfried D. Schubert; Hye-Mi Kim; Daehyun Kim; Hyun-Suk Kang; Hyun-Kyung Kim; Craig MacLachlan; Adam A. Scaife (Climate Dynamics, 2019)

Spatial Variability and Long-Term Trend in the Occurrence Frequency of Heatwave and Tropical Night in Korea - Nakbin Choi; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Intercomparison of Terrestrial Carbon Fluxes and Carbon Use Efficiency Simulated by CMIP5 Earth System Models - Dongmin Kim; Myong-In Lee; Su-Jong Jeong; Jungho Im; Dong Hyun Cha; Sanggyun Lee (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Increase in the potential predictability of the Arctic Oscillation via intensified teleconnection with ENSO after the mid-1990s - Daehyun Kang; Myong-In Lee (Climate Dynamics, 2017)

Cloud radiative effects and changes simulated by the Coupled Model Intercomparison Project Phase 5 models - Sun-Hee Shin; Ok-Yeon Kim; Dongmin Kim; Myong-In Lee (Advances in Atmospheric Sciences, 2017)

Dynamical–statistical seasonal prediction for western North Pacific typhoons based on APCC multi-models - Ok-Yeon Kim; Hye-Mi Kim; Myong-In Lee; Young-Mi Min (Climate Dynamics, 2017)

Interannual variability of heat waves in South Korea and their connection with large‐scale atmospheric circulation patterns - Woo‐Seop Lee; Myong‐In Lee (International Journal of Climatology, 2016)
This study investigates the interannual variation of heat wave frequency ( HWF ) in South Korea during the past 42 years (1973–2014) and examines its connection with large‐scale atmospheric circulation changes. Korean heat waves tend to develop most frequently in late summer during July and August. The leading Empirical Orthogonal Function accounting for 50% of the total variance shows a mono‐signed pattern over South Korea, suggesting that the dominant mechanisms responsible for the heat wave are linked in a spatial scale much larger than the nation. It also exhibits a regional variation with more occurrences in the southeastern inland area. The regression of the leading principal component ( PC ) time series of HWF with large‐scale atmospheric circulation identifies a north–south dipole pattern between the South China Sea and Northeast Asia. When this large‐scale circulation mode facilitates deep convection in South China Sea, it tends to weaken moisture transport from the South China Sea to Northeast Asia. Enhanced deep convection in the South China Sea triggers a source of Rossby wave train along southerly wind that generates positive geopotential height anomalies around Korea. The anomalous high pressure pattern is accompanied by large‐scale subsidence in Korea, thereby providing a favourable condition for extreme hot and dry days in Korea. This study highlights that there is a decadal change of the relationship between Korean heat waves and large‐scale atmospheric circulation patterns. The tropical forcing tends to be weakened in the recent decade, with more influences from the Arctic variability from the mid‐1990s.

El Niño and Indian summer monsoon rainfall relationship in retrospective seasonal prediction runs: experiments with coupled global climate models and MMEs - P. K. Pradhan; Venkatraman Prasanna; Doo Young Lee; Myong-In Lee (Meteorology and Atmospheric Physics, 2016)

Spatial and diurnal variations of storm heights in the East Asia summer monsoon: storm height regimes and large-scale diurnal modulation - Myung-Sook Park; Myong-In Lee; Hyerim Kim; Jungho Im; Jung-Moon Yoo (Climate Dynamics, 2016)

Erratum to: Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Examinations of cloud variability and future change in the coupled model intercomparison project phase 3 simulations - Sun-Hee Shin; Myong-In Lee; Ok-Yeon Kim (Asia-Pacific Journal of Atmospheric Sciences, 2014)

Representation of tropical subseasonal variability of precipitation in global reanalyses - Daehyun Kim; Myong-In Lee; Dongmin Kim; Siegfried D. Schubert; Duane E. Waliser; Baijun Tian (Climate Dynamics, 2014)

Validation of the experimental hindcasts produced by the GloSea4 seasonal prediction system - Myong-In Lee; Hyun-Suk Kang; Daehyun Kim; Dongmin Kim; Hyerim Kim; Daehyun Kang (Asia-Pacific Journal of Atmospheric Sciences, 2014)

Chronological changes in inflammatory cytokines immunoreactivities in the mouse hippocampus after systemic administration of high dosage of tetanus toxin - Bing Chun Yan; Joon Ha Park; In Hye Kim; Bich Na Shin; Ji Hyeon Ahn; Ki-Yeon Yoo; Deuk-Sik Lee; Myong Jo Kim; Il-Jun Kang; Moo-Ho Won (Experimental Brain Research, 2012)

Simulation of the intraseasonal variability over the Eastern Pacific ITCZ in climate models - Xianan Jiang; Duane E. Waliser; Daehyun Kim; Ming Zhao; Kenneth R. Sperber; William F. Stern; Siegfried D. Schubert; Guang J. Zhang; Wanqiu Wang; Marat Khairoutdinov; Richard B. Neale; Myong-In Lee (Climate Dynamics, 2012)

Natural 15N abundance of paddy rice (Oryza sativa L.) grown with synthetic fertilizer, livestock manure compost, and hairy vetch - Soek-In Yun; Sang-Sun Lim; Gwang-Sung Lee; Sang-Mo Lee; Han-Yong Kim; Hee-Myong Ro; Woo-Jung Choi (Biology and Fertility of Soils, 2011)

Representation of tropical storms in the northwestern pacific by the Modern-Era Retrospective analysis for research and applications - Myong-In Lee; Siegfried D. Schubert; Dongmin Kim (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Suppression of NH3 and N2O emissions by massive urea intercalation in montmorillonite - Kwang Seop Kim; Man Park; Choong Lyeal Choi; Dong Hoon Lee; Young Jin Seo; Chan Yong Kim; Jong Su Kim; Seok-In Yun; Hee-Myong Ro; Sridhar Komarneni (Journal of Soils and Sediments, 2011)

Mechanisms of diurnal precipitation over the US Great Plains: a cloud resolving model perspective - Myong-In Lee; Ildae Choi; Wei-Kuo Tao; Siegfried D. Schubert; In-Sik Kang (Climate Dynamics, 2010)